FORMULASI SEDIAAN HAND BODY LOTION ANTIPENUAAN DARI KOMBINASI TANAMAN KOMODITAS HORTIKULTURA EKSTRAK BUAH PEPAYA DAN STROBERI DALAM MENGHAMBAT ENZIM TIROSINASE - Firman Rezaldi; Vevi Maritha; Muhammad Faizal Fathurrohim; Andri Tri Cahyono; Dyah Rohmawati; Sukardi Sugeng Rahmad; Roni Gumilar; Ratna Fitry Yenny (Sekolah Tinggi Ilmu Kesehatan Tujuh Belas, Karanganyar, JAwa, Indonesia, 2022)
One of the long-term losses in homeostatic balance in every living creature is a sign of aging skin. Hyperpigmentation conditions caused by the activity of the tyrosinase enzyme are an indicator of aging. One of the solutions that can be applied to prevent premature signs of aging is skin care using the most affordable pharmaceutical preparation, namely Hand Body Lotion. Hand Body Lotion which has anti-aging properties can be produced from bioactive compounds from horticultural commodity plants because it has been proven and is quite popular. Apart from being able to be used as an active ingredient in functional food, it can also be recommended as a pharmaceutical, namely the preparation of active cosmetic ingredients. This is because the content of vitamins, antioxidants, essential oils, proteins, even phenolic compounds and other active ingredients which are quite environmentally friendly can be produced from horticultural commodity plants, especially in the fruit group used in this research. Strawberry fruit has been reported to contain organic compounds such as gallic acid, elagic acid, and ferulic acid which can inhibit the melanogenesis process both in vitro and in vivo from previous findings. Papaya fruit contains saponins, flavonoids, alkaloids and tannins so it can be designed to inhibit the tyrosinase enzyme. This research aims to determine the inhibitory power of the tyrosinase enzyme from horticultural commodity plant extracts, both strawberries and papaya, in the form of formulations and hand body lotion preparations. The results of this research have proven that based on the IC50 value of horticultural commodity plant extracts, papaya has better inhibitory power for the tyrosinase enzyme compared to strawberries, namely 8,875 µg/mL. The conclusion in this research is that horticultural commodity plants in the form of papaya fruit extract are more recommended as an active ingredient in inhibiting the tyrosinase enzyme when compared with strawberry fruit extract based on the IC50 value even though in the form of hand body lotion it has the potential to inhibit the tyrosinase enzyme.